Effective dissociation temperature for estimation of electric arc plasma composition - Babich, I.L.; Boretskij, V.F.; Veklich, A.N. (Вопросы атомной науки и техники, 2011)
Spectroscopy investigations of the thermal multicomponent plasma of the electric arc discharge between copper electrodes in carbon dioxide flow were carried out. The technique of calculation of plasma equilibrium composition is discussed. The influence of thermal dissociation of molecular gas on the plasma state is estimated. It was assumed that the thermal dissociation of molecules of working gas play the key role in deviation from local thermodynamic equilibrium (LTE) in plasma.